Enhanced artificial bee colony algorithm with mobile sink management to improve network lifetime in WSN - et. al., Ms. Apurva Saoji, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Traditionally wireless sensor network uses multi-hop routing to transmit the data from source node to the sink. Many problems arise due to multi hop routing, the common problem is hotspot problem and transmission overhead. The paper has propose mobile sink based algorithm for Collection of data in wireless sensor network. Data Collection will be encouraged with efficient cluster head selection and enhanced artificial Bee Colony algorithm (EABC). Analysis of the proposed method with existing research methods has been done. Simulation results shows that proposed algorithm can effectively reduce transmission overload, and improve network lifetime, when compared with similar ant Colony algorithm and traditional LEACH methodology. Effective management of mobile sink and exploring shortest path through it proves efficient in energy Optimization of wireless sensor network.